Better care for less money: cost‐effectiveness of integrated care in multi‐episode patients with severe psychosis. (12th January 2020) - Karow, A.; Brettschneider, C.; Helmut König, H.; Correll, C.U.; Schöttle, D.; Lüdecke, D.; Rohenkohl, A.; Ruppelt, F.; Kraft, V.; Gallinat, J.; Lambert, M.
Abstract : Objective: To compare cost‐effectiveness of integrated care with therapeutic assertive community treatment (IC‐TACT) versus standard care (SC) in multiple‐episode psychosis. Method: Twelve‐month IC‐TACT in patients with schizophrenia‐spectrum and bipolar I disorders were compared with a historical control group. Primary outcomes were entropy‐balanced cost‐effectiveness based on mental healthcare costs from a payers' perspective and quality‐adjusted life years (QALYs) as a measure of health effects during 12‐month follow‐up. Results: At baseline, patients in IC‐TACT ( n  = 214) had significantly higher illness severity and lower functioning than SC ( n  = 56). Over 12 months, IC‐TACT had significantly lower days in inpatient (10.3 ± 20.5 vs. 28.2 ± 44.9; P  = 0.005) and day‐clinic care (2.6 ± 16.7 vs. 16.4 ± 33.7; P  = 0.004) and correspondingly lower costs (€−55 084). Within outpatient care, IC‐TACT displayed a higher number of treatment contacts (116.3 ± 45.3 vs. 15.6 ± 6.3) and higher related costs (€+1417). Both resulted in lower total costs in IC‐TACT (mean difference = €−13 248 ± 2975, P  < 0.001). Adjusted incremental QALYs were significantly higher for IC‐TACT versus SC (+0.10 ± 0.37, P  = 0.05). The probability of cost‐effectiveness of IC‐TACT was constantly higher than 99%. Conclusion: IC‐TACT was cost‐effective compared with SC. The use of prima facies 'costly' TACT teams is highly recommended to improve outcomes and save total cost for patients with severe psychotic disorders.